2016
DOI: 10.1111/ijau.12069
|View full text |Cite
|
Sign up to set email alerts
|

Auditor Tenure and Perceived Earnings Quality

Abstract: The study examines how auditor tenure affects investors' perception of audit quality. It is motivated by the ongoing debate on the effect of auditor tenure on audit quality and the recent regulation approval on mandatory auditor rotation at the EU level, which is justified by the concern that longer auditor tenure impairs auditor independence and thus lowers audit quality. Perceived earnings quality, as measured by the earnings response coefficient from returns‐earnings regression, is used as a proxy for inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 80 publications
3
19
0
5
Order By: Relevance
“…In order to check the robustness concerning audit tenure, indicator variables for short (< 4 years) and long (> 10 years) tenure are tested. The threshold for short tenure was used in prior German studies by Quick and Wiemann (2011), Wiemann (2012), andHohenfels (2016). The threshold for long tenure is based on the recent EU regulation, which generally requires a mandatory auditor rotation after ten years for firms of public interest (EU Parliament, 2014, Art.…”
Section: Market-adjusted Returns and Crisis Effectsmentioning
confidence: 99%
“…In order to check the robustness concerning audit tenure, indicator variables for short (< 4 years) and long (> 10 years) tenure are tested. The threshold for short tenure was used in prior German studies by Quick and Wiemann (2011), Wiemann (2012), andHohenfels (2016). The threshold for long tenure is based on the recent EU regulation, which generally requires a mandatory auditor rotation after ten years for firms of public interest (EU Parliament, 2014, Art.…”
Section: Market-adjusted Returns and Crisis Effectsmentioning
confidence: 99%
“…;Hosseini et al (2016);Lobo et al (2017) found a positive association between firm size and ERC. The high level of debt of the company encourages systemic risk of investment, so the level of debt has a negative impact on the ERC(Hohenfels, 2016).Collins and Kothari (1989) found a positive association between growth opportunities to the rate of return on shares and company profits Lee & Yoon (2012)Hosseini et al (2016) control growth opportunities to examine the effect of independent variables on market response Hosseini et al (2016)…”
mentioning
confidence: 99%
“…Os autores analisaram a situação para os períodos pré e pós Lei Sarbanes -Oxley (SOX) e identificaram que esses efeitos deixam de existir após a SOX, evidenciando que os mecanismo implementados pela referida lei foram eficazes e que não há, portanto, a necessidade de rodízio mandatório de firmas de auditoria. Hohenfels (2016), considerando a percepção dos investidores sobre a qualidade da auditoria através do coeficiente de resposta de lucros (Earning Response Coefficient -ERC) numa regressão retorno-lucro, estudou os impactos da tenure sobre a qualidade para empresas listadas na bolsa de Frankfurt. Verificou-se neste estudo uma relação não linear entre a qualidade percebida e a tenure, sugerindo que a qualidade percebida é menor nos anos iniciais e finais do relacionamento auditor-auditado.…”
Section: (V) Rodízio Mandatório De Firmas E a Reação Do Mercado De Caunclassified
“…A equação 3.6 é uma simplificação da equação 3.5, tratando agora a relação da qualidade da auditoria com o tempo de relacionamento auditor-auditado (tenure) como uma função quadrática. Esse tipo de modelo já foi empregado na literatura em alguns trabalhos, como é o caso de Chi e Huang (2005), Boone et al (2008), Davis et al (2009), Hohenfels (2016) e Brooks et al (2017). Uma desvantagem desta abordagem é que ela não permite separar as contribuições individuais do aumento da competência técnica e da diminuição da independência, impedindo assim a identificação dos fatores que mais poderiam influenciar o tempo adequado para o rodízio de auditoria.…”
Section: Modelo Quadráticounclassified
See 1 more Smart Citation